2006
DOI: 10.1152/ajpcell.00505.2005
|View full text |Cite
|
Sign up to set email alerts
|

Release of iron from ferritin requires lysosomal activity

Abstract: Kidane, Theodros Z., Eric Sauble, and Maria C. Linder. Release of iron from ferritin requires lysosomal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
199
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 48 publications
7
199
1
2
Order By: Relevance
“…Treatment with this Fe(III) chelator for 15 minutes resulted in a significant increase in "free" iron signal (figure 3). Although based on other studies it is known that desferrioxamine treatment for 15 minutes using similar concentrations does not release additional iron into "free" iron pool from iron containing proteins [20,21,33], we carried out fractionation experiments to separate low molecular weight fractions from high molecular weight fractions containing iron. Our study conclusively proved that even up to 2 hour incubation with desferrioxamine does not release iron from high molecular weight iron containing species into low molecular weight iron pool as measured by ICP-MS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with this Fe(III) chelator for 15 minutes resulted in a significant increase in "free" iron signal (figure 3). Although based on other studies it is known that desferrioxamine treatment for 15 minutes using similar concentrations does not release additional iron into "free" iron pool from iron containing proteins [20,21,33], we carried out fractionation experiments to separate low molecular weight fractions from high molecular weight fractions containing iron. Our study conclusively proved that even up to 2 hour incubation with desferrioxamine does not release iron from high molecular weight iron containing species into low molecular weight iron pool as measured by ICP-MS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of lysosomes in ferritin degradation and the concomitant iron release has been shown in different cell lines exposed to iron chelating agents (particularly deferoxamine (DFO) or overexpression of FtMt) (Kidane et al 2006;Zhang et al 2010), bacterial infection (Larson et al 2004), and ferroportin activation (Asano et al 2011). Lysosomal inhibitors, but not proteasomal inhibitors, could halt the degradation, induce ferritin accumulation in the organelles and block iron release.…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…When stored iron is needed for synthesis of iron-containing structures, it has to be released from ferritin. Recent research has shown that the major mechanism for this iron release involves lysosomal digestion (Bridges and Hoffman, 1986, Garner et al, 1998, Kidane et al, 2006, Konijn et al, 1999, Kurz et al, 2011, Kwok and Richardson, 2004, Persson et al, 2003, Radisky and Kaplan, 1998, Roberts and Bomford, 1988, Sakaida et al, 1990, Tenopoulou et al, 2005, Vaisman et al, 1997, Yu et al, 2003b, Zhang et al, 2010. Iron is then relocated to the cytoplasm, probably by the participation of DMT1.…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%